Indocyanine green angiography for lower incidence of anastomotic leakage after transanal total mesorectal excision: a propensity score-matched cohort study - Chen, Hengkai; Ye, Linfang; Huang, Changyu; Shi, Yingjun; Lin, Fangzhou; Ye, Honghao; Huang, Yongjian (Frontiers in Oncology, 2023)
Background Anastomotic leakage (AL) is the most serious complication that can arise during colorectal surgery. Indocyanine green (ICG) angiography offers an intraoperative assessment of colonic vascular perfusion in real time. We aimed to assess ICG’s effects on the AL rate in patients who have undergone transanal total mesorectal excision (TaTME) for rectal cancer. Methods This retrospective cohort study was conducted at our center from October 2018 to March 2022 to analyze the clinical data of patients with rectal cancer who have undergone TaTME after propensity score matching (PSM). The primary outcome was the proximal colonic transection line modification and clinical AL rate. Results A total of 143 patients in the non-ICG group and 143 patients in the ICG group were included after PSM. The proximal colonic transection line of seven patients in the non-ICG group was modified, while 18 were in the ICG group (4.9% vs. 12.5%, p = 0.023). Twenty-three patients (16.1%) in the non-ICG group and five patients (3.5%) in the ICG group were diagnosed with AL (p < 0.001). The ICG group had a less hospital readmission rate than the non-ICG group (0.7% vs. 7.7%, p = 0.003). The between-group differences in basic line and other outcomes were not significant. Conclusions ICG angiography is a safe and feasible method to help surgeons identify potentially poor colonic vascular perfusion and modify the proximal colonic transection line, resulting in a significant reduction in AL and hospital readmission rates.